Digital Transformation of Maritime Education Management: Technology-Based Performance Systems and Lecturer Productivity in Indonesian Institutions - Suhartini Suhartini; Marudut Bernadtua Simanjuntak (Universitas Muhammadiyah Mataram, 2026)
Digital transformation fundamentally reshapes academic work environments, yet maritime education institutions under Ministry of Transportation governance face distinctive challenges implementing technology-based management systems while maintaining lecturer wellbeing and institutional effectiveness. This convergent parallel mixed-methods research investigates how digital performance monitoring platforms, administrative systems, learning analytics, and e-leadership practices influence lecturer job satisfaction, organizational commitment, technostress, research productivity, and teaching effectiveness across fourteen Indonesian maritime higher education institutions. Through in-depth interviews with 425 lecturers, 58 administrators, 42 policy officials, and 35 technology specialists, combined with focus groups, organizational ethnography, and thematic analysis, this study reveals paradoxical technology impacts: while certain systems enhanced efficiency and pedagogical innovation, poorly implemented digital tools increased administrative burden (91% reporting), reduced perceived autonomy (87%), elevated technostress (64%), and negatively affected job satisfaction (71% negative intrinsic satisfaction). Critical moderating factors emerged including e-leadership effectiveness (91% successful implementations), participatory implementation approaches (88%), comprehensive professional development (87%), user-centered system design (94%), and robust technical support (84%). The research contributes the Maritime Academic Technology Impact Framework (MATIF) providing evidence-based implementation guidelines for administrators and policy officials pursuing digital transformation while protecting academic workforce sustainability within Ministry of Transportation governance contexts.